Exploring County Lines: Criminal Drug Distribution Practices in Scotland. (April 2020) - Holligan, Chris; McLean, Robert; McHugh, Richard
The concept of 'County Lines' denotes an exploitative type of illegal drug distribution and dealing criminal enterprise that is indicative of the development of new strategies to underpin criminal markets in Britain. It is a growing phenomenon characterizing the evolution and working of drug distribution networks in contemporary Britain which often establish 'nests' in the homes of vulnerable persons domiciled within drug traffic hubs. This article draws upon qualitative data generated from interviews with active and former offenders and members of intervention agencies in order to understand more about the denizens of this embryonic criminal world.